The effect of perioperative hemadsorption in patients operated for acute infective endocarditis—A randomized controlled study. Issue 11 (5th July 2021) - Asch, Silke; Kaufmann, Tobias Peter; Walter, Michaela; Leistner, Marcus; Danner, Bernd C.; Perl, Thorsten; Kutschka, Ingo; Niehaus, Heidi
Abstract: Patients operated for infective endocarditis (IE) are at high risk of developing an excessive systemic hyperinflammatory state, resulting in systemic inflammatory response syndrome and septic shock. Hemoadsorption (HA) by cytokine adsorbers has been successfully applied to remove inflammatory mediators. This randomized controlled trial investigates the effect of perioperative HA therapy on inflammatory parameters and hemodynamic status in patients operated for IE. A total of 20 patients were randomly assigned to either HA therapy or the control group. HA therapy was initiated intraoperatively and continued for 24 hours postoperatively. Cytokine levels (IL‐6, IL‐1b, TNF‐α), leukocytes, C‐reactive protein (CRP), and Procalcitonin (PCT) as well as catecholamine support, and volume requirement were compared between both groups. Operative procedures included aortic (n = 7), mitral (n = 6), and multiple valve surgery (n = 7). All patients survived to discharge. No significant differences concerning median cytokine levels (IL‐6 and TNF‐α) were observed between both groups. CRP and PCT baseline levels were significantly higher in the HA group (59.5 vs. 26.3 mg/dL, P  = .029 and 0.17 vs. 0.05 µg/L, P  = .015) equalizing after surgery. Patients in the HA group required significantly higher doses of vasopressors (0.093 vs. 0.025 µg/kg/min norepinephrine, P  = .029) at 12 hours postoperatively as well as significantly more overall volume replacement (7217 vs. 4185 mL at 12 hours, P  = .015; 12 021 vs. 4850 mL at 48 hours, P  = .015). HA therapy did neither result in a reduction of inflammatory parameters nor result in an improvement of hemodynamic parameters in patients operated for IE. For a more targeted use of HA therapy, appropriate selection criteria are required. Abstract : The perioperative use of cytokine adsorption via hemadsorption did neither reduce inflammatory parameters nor improve hemodynamic parameters in patients operated for infective endocarditis.